Tradisi Mangompa Manuk dalam Pesta Adat Pernikahan Masyarakat Mandailing Natal Perspektif Urf - Nst, Lisca Anggina; Irwan, Irwan (UNES Law Review, 2023)
The tradition of Mangompa Manuk at wedding ceremony in the Mandailing Natal community has been a tradition passed down from generation to generation. Indigenous people regard that if they do not carry out this tradition, their marriage is invalid. The aim of this research is to determine the customs and traditions of Mangompa Manuk in carrying out weddings in Gunung Tua Village, Panyabungan District, Mandailing Natal Regency. Beside that, it aims to find out how the mangompa manuk tradition began, the purpose of mangompa manuk and why it still develops in the middle of Gunung Tua Village’s civilations, Panyabungan District, Mandailing Natal Regency and how about the society’s view if they don’t carry out this tradition, what are their motives when carrying out the mangompa manuk tradition, how is mangompa manuk tradition in the urf perspectife, is it appropriate with islamic law? or whether it is contrary to islamic law. The method of research is qualitative method that used to produced descriptive data in the Form, of written or spoken words from traditional figures, such as Hatobangan, traditional society, Religious Leaders, Muhammadiyah, figures and head MUI in Gunung Tua Village, Panyabungan district, Mandailing Natal Regency.